RANCANG BANGUN TEOLOGI LOKAL SANGKAN PARAN BAGI PEWARTAAN INJIL DI PAGUYUBAN NGESTI TUNGGAL CARUBAN - Yehudha Andrew Sugito; Aji Suseno (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
The encounter between the Gospel and culture often creates tensions. Some of these tensions can be found in some issues of evangelization in the midst of Indonesia's diverse ethnicities and cultures. Local theology is both a strategy and a way out of this problem. Designing and building local theology must be connected to local cultural values. One of the local cultural values raised in this research is sangkan paran found in the Javanese community in Paguyuban Ngesti Tunggal (Pangestu). Through qualitative research methods using interviews, documents and desk research, the values of sangkan paran are explored and assessed from a biblical perspective, resulting in several findings. The findings show many points of convergence as well as points of difference between Pangestu's concept of sangkan paran and that of the Bible. All of these findings become material for the design of local theology that is actualized in the proclamation of the Gospel to the Javanese community in Pangestu Caruban.